Pengaruh Marketing Mix Terhadap Keputusan Pembelian Produk Sulaman Khas Kota Padang - Irwannus Pratama; Rose Rahmidani (Jurnal Ecogen, 2020)
This study aims to determine the effect of marketing mix on the typical purchasing decisions of Padang City products. This research is a causative descriptive study. The population in this study were people who had used a special embroidery in Padang City using primary data. The sampling technique uses incidental sampling. The number of samples in this study were 100 respondents. The data analysis method used is to use path analysis in the SPSS version 23. The results of the study show that: (1) the product has a significant positive effect on the purchase decisions of a typical City of Padang embroidery, (2) the price has a significant positive effect on the purchase purchase of typical City of Padang decisions, (3) the location has a significant positive effect on the purchase decision of Padang, (4) promotion does not have a significant effect on the purchase decision of a typical Padang embroidery.Keywords: products, prices, location, promotion, and purchasing decisions